Instructional modules for secondary social studies I effects on academic achievement and attitudes of students - Gajardo, Melanie Serrano (2006)
This study was conducted to improve the teaching-learning processes particularly in Social Studies. The instructional modules were written specifically for First Year students of Labangal National High School, General Santos City. The mean level of attitudes of the students taught with modular instruction is lower compared to the mean level of attitudes of the students taught by the conventional method. Hence, modular instruction can improve academic achievement. It was suggested that administrators be given a chance for their teachers to avail of seminars/training for better learning outcomes. Social Studies teachers are encouraged to adapt the use of Instructional Modules in teaching Araling Panlipunan to make lessons more interesting and meaningful and to provide independent study.